Evidence of substrate control of Cdk phosphorylation during the budding yeast cell cycle - Luca Takacs; Lina Gerontogianni; Kimberly Quililan; Helen Flynn; Frank Uhlmann (Cell Reports)
Summary: A series of sequential events orchestrates cell growth and division, set in motion by cyclin-dependent kinases (Cdks). In the “qualitative model” for Cdk control, order is achieved by cell cycle stage-specific cyclins. However, single-cyclin cells retain cell cycle order. In an alternative “quantitative model,” increasing Cdk activity triggers substrate phosphorylation at sequential thresholds. Here, we test a key prediction from the quantitative model: the best Cdk substrates should be the first to be phosphorylated. Phosphoproteome analysis of synchronous budding yeast cultures, against expectations, reveals little correlation between known in vitro Cdk phosphorylation rates and observed in vivo phosphorylation timing. Incorporating Cdk-counteracting phosphatases that impose phosphorylation thresholds does not improve the correlation. Instead of kinase-phosphatase control (i.e., “regulator control”), our phosphoproteome patterns reveal signatures of “substrate control,” including substrate-defined phosphorylation waves. The changing behavior of the substrates themselves therefore contributes to ordering their Cdk phosphorylation during the budding yeast cell cycle.